Mechanochemical green synthesis of hyper-crosslinked cyclodextrin polymers - Rubin Pedrazzo, Alberto; Caldera, Fabrizio; Zanetti, Marco; Appleton, Silvia Lucia; Dhakar, Nilesh Kumar; Trotta, Francesco (Beilstein Journal of Organic Chemistry, 2020)
Cyclodextrin nanosponges (CD-NS) are nanostructured crosslinked polymers made up of cyclodextrins. The reactive hydroxy groups of CDs allow them to act as multifunctional monomers capable of crosslinking to bi- or multifunctional chemicals. The most common NS synthetic pathway consists in dissolving the chosen CD and an appropriate crosslinker in organic polar aprotic liquids (e.g., N,N-dimethylformamide or dimethyl sulfoxide), which affect the final result, especially for potential biomedical applications. This article describes a new, green synthetic pathway through mechanochemistry, in particular via ball milling and using 1,1-carbonyldiimidazole as the crosslinker. The polymer obtained exhibited the same characteristics as a CD-based carbonate NS synthesized in a solvent. Moreover, after the synthesis, the polymer was easily functionalized through the reaction of the nucleophilic carboxylic group with three different organic dyes (fluorescein, methyl red, and rhodamine B) and the still reactive imidazoyl carbonyl group of the NS.
Keywords: β-cyclodextrin; ball-milling; crosslinking; green chemistry; mechanochemistry; nanosponges

(untitled) - Caldera, F.; Tannous, M.; Cavalli, R.; Zanetti, M.; Trotta, F. (Int. J. Pharm., 2017)

Cyclodextrins in Pharmaceutics, Cosmetics and Biomedicine: Current and Future Industral Applications - Trotta, F. (Cyclodextrin Nanosponges and their Applications, 2011)

(untitled) - Trotta, F.; Zanetti, M.; Cavalli, R. (Beilstein J. Org. Chem., 2012)

(untitled) - Trotta, F.; Caldera, F.; Cavalli, R.; Soster, M.; Riedo, C.; Biasizzo, M.; Uccello Barretta, G.; Balzano, F.; Brunella, V. (Expert Opin. Drug Delivery, 2016)

(untitled) - Trotta, F.; Dianzani, C.; Caldera, F.; Mognetti, B.; Cavalli, R. (Expert Opin. Drug Delivery, 2014)

(untitled) - Swaminathan, S.; Cavalli, R.; Trotta, F. (Wiley Interdiscip. Rev.: Nanomed. Nanobiotechnol., 2016)

(untitled) - Cavalli, R.; Trotta, F.; Tumiatti, W. (J. Inclusion Phenom. Macrocyclic Chem., 2006)

(untitled) - Krabicová, I.; Appleton, S. L.; Tannous, M.; Hoti, G.; Caldera, F.; Rubin Pedrazzo, A.; Cecone, C.; Cavalli, R.; Trotta, F. (Polymers (Basel, Switz.), 2020)

PCT Pat. Appl. - Trotta, F.; Shende, P.; Biasizzo, M. (Method for Preparing Dextrin Nanosponges, 2012)

Green Chemistry: Theory and Practice - Anastas, P. T.; Warner, J. C. (Oxford University Press, 1998)

(untitled) - Takacs, L. (Chem. Soc. Rev., 2013)

(untitled) - Burmeister, C. F.; Kwade, A. (Chem. Soc. Rev., 2013)

(untitled) - Wang, X.; Sun, F.; Huang, Y.; Duan, Y.; Yin, Z. (Chem. Commun., 2015)

(untitled) - Willis-Fox, N.; Rognin, E.; Aljohani, T. A.; Daly, R. (Chem, 2018)

(untitled) - Lanzillotto, M.; Konnert, L.; Lamaty, F.; Martinez, J.; Colacino, E. (ACS Sustainable Chem. Eng., 2015)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Andersen, J.; Mack, J. (Green Chem., 2018)

(untitled) - Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2019)

(untitled) - Gilet, A.; Quettier, C.; Wiatz, V.; Bricout, H.; Ferreira, M.; Rousseau, C.; Monflier, E.; Tilloy, S. (Green Chem., 2018)

(untitled) - Gan, T.; Zhang, Y.; Su, Y.; Hu, H.; Huang, A.; Huang, Z.; Chen, D.; Yang, M.; Wu, J. (Cellulose, 2017)

(untitled) - Jicsinszky, L.; Caporaso, M.; Calcio Gaudino, E.; Giovannoli, C.; Cravotto, G. (Molecules, 2017)

(untitled) - Jicsinszky, L.; Tuza, K.; Cravotto, G.; Porcheddu, A.; Delogu, F.; Colacino, E. (Beilstein J. Org. Chem., 2017)

(untitled) - Cravotto, G.; Caporaso, M.; Jicsinszky, L.; Martina, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Ogoshi, T.; Harada, A. (Sensors, 2008)

(untitled) - Kuwabara, T.; Nakajima, H.; Nanasawa, M.; Ueno, A. (Anal. Chem. (Washington, DC, U. S.), 1999)

(untitled) - Mieszawska, A. J.; Kim, Y.; Gianella, A.; van Rooy, I.; Priem, B.; Labarre, M. P.; Ozcan, C.; Cormode, D. P.; Petrov, A.; Langer, R.; Farokhzad, O. C.; Fayad, Z. A.; et al. (Bioconjugate Chem., 2013)

(untitled) - Becuwe, M.; Landy, D.; Delattre, F.; Cazier, F.; Fourmentin, S. (Sensors, 2008)

(untitled) - Huang, J.; Weinfurter, S.; Pinto, P. C.; Pretze, M.; Kränzlin, B.; Pill, J.; Federica, R.; Perciaccante, R.; Ciana, L. D.; Masereeuw, R.; Gretz, N. (Bioconjugate Chem., 2016)

(untitled) - Wang, G. W. (Chem. Soc. Rev., 2013)

(untitled) - Dhakar, N. K.; Caldera, F.; Bessone, F.; Cecone, C.; Pedrazzo, A. R.; Cavalli, R.; Dianzani, C.; Trotta, F. (Carbohydr. Polym., 2019)

(untitled) - Staab, H. A. (Angew. Chem., Int. Ed. Engl., 1962)

(untitled) - Trotta, F.; Moraglio, G.; Marzona, M.; Maritano, S. (Gazz. Chim. Ital., 1993)

(untitled) - Jadhav, S. A.; Karande, S. D.; Burungale, S. H. (Mater. Des. Process. Commun., 2019)